Management Geography - Making Place for Space in Management Thought - Lech Suwala; Piotr Pachura; Rolf Dieter Schlunze (Polish Journal of Management Studies, 2022)
The purpose of the paper is to introduce the interdisciplinary research stream called Management geography towards the broadly defined field of management studies. Management geography is targeting the nexus between 'space and management' and encompasses the study of spatial factors, spatial dimensions and spatial conditions of management processes in, by and between organizations. Research about space is not well established in management thought. Space is predominantly investigated within the borders of the organization, is imagined only implicitly, and will generally be substituted by strategy, structure, control, hierarchy, or other organizing elements. Management was born as a hands-on discipline, thus avoiding getting entangled in abstract phenomena or concepts like space or just taking them for granted. By providing a focused overview of the understandings of space in classical management theory and recent approaches, we outline shortcomings, unexploited potentials and new avenues necessary to address current spatial challenges in a globalized and hyperconnected world through the lenses of Management geography. Results highlight that understanding spaces, in particular, also between and outside of the organization can contribute to both explaining managerial and organizational success or failure as a spatial differentiating factor and allowing for a more balance approach towards the multifaceted management coordination of spaces in, by, between and around organizations.
Keywords: M10; P25; R10; O18; 650; management geography; management; space; business; organization